2020
DOI: 10.1097/corr.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Does a Reduced Number of Muscle Stem Cells Impair the Addition of Sarcomeres and Recovery from a Skeletal Muscle Contracture? A Transgenic Mouse Model

Abstract: Background Children with cerebral palsy have impaired muscle growth and muscular contractures that limit their ROM. Contractures have a decreased number of serial sarcomeres and overstretched lengths, suggesting an association with a reduced ability to add the serial sarcomeres required for normal postnatal growth. Contractures also show a markedly reduced number of satellite cells—the muscle stem cells that are indispensable for postnatal muscle growth, repair, and regeneration. The potential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…Several studies have investigated factors that influence satellite cell number and muscle regeneration, yet the link between satellite cells and recovery of strength has been minimally studied. Combining satellite cell ablation and hindlimb casting to model muscle contractures, Dayanidhi, Kinney, Dykstra, and Lieber (2020) showed that a reduced number of satellite cells impaired muscle's ability to add sarcomeres in series and recover from the immobilization‐induced contracture. That study suggested that there is a relationship between satellite cell number and muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated factors that influence satellite cell number and muscle regeneration, yet the link between satellite cells and recovery of strength has been minimally studied. Combining satellite cell ablation and hindlimb casting to model muscle contractures, Dayanidhi, Kinney, Dykstra, and Lieber (2020) showed that a reduced number of satellite cells impaired muscle's ability to add sarcomeres in series and recover from the immobilization‐induced contracture. That study suggested that there is a relationship between satellite cell number and muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…These features could explain the difficulties that children with CP experience in recovering from an immobilization-induced contracture. Moreover, in these patients, the low addition of serial sarcomere number could be due to a decreased number of SCs (Dayanidhi et al, 2020). Unfortunately, the onset and development of these muscle alterations are not well understood, because data from young patients with CP, i.e., <10 years of age, are still unavailable.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 While the regulation of muscle length and its contribution to skeletal muscle growth/development are not well characterized, prior studies have posited a role for muscle stem cells (satellite cells) in governing the length of a muscle. 16 18 To scrutinize the role of satellite cells in denervation-induced muscle growth deficits, we utilized a transgenic mouse line to inhibit satellite cell fusion, 19 , 20 thereby blocking subsequent addition of myonuclei to growing multinucleated myofibers (myonuclear accretion). 21 Intriguingly, we discovered that complete neonatal denervation does not impair myonuclear accretion, and that neonatal inhibition of myonuclear accretion does not impair longitudinal muscle growth.…”
Section: Introductionmentioning
confidence: 99%